Return to cycling after hip arthroplasty: a case report of femoroacetabular impingement - Anhalt, R.; Löbell, R.; Fagundes, F. P.; Saccol, M. F. (Journal of Science and Cycling, 2021)
This study aims to describe the pre and postoperative functional deficits of a recreational cycling athlete diagnosed with severe femoroacetabular impingement. Assessments were performed before, and at 8 and 24 months after total hip arthroplasty using patient reported outcome measures and strength assessment. The participant presented a progressive improvement in postoperative assessment regarding pain and function according to the Western Ontario and McMaster Universities Osteoarthritis Index and the Lower Extremity Functional Scale. There was a reduction in the time to perform the Time Up and Go Test and an improvement of strength deficits, especially in abductors (deficit from 64.8% to 6.5% in the pre versus post 24 months) and hip adductors (deficit from 30% to 15,7% in the pre versus post 24 months). The return to cycling occurred gradually after surgery, showing the efficacy and good responsiveness to treatment.